Negative life events and depression among Chinese university freshmen: a longitudinal moderated mediation model - Pei Jiang; Zhihui Zhang; Shuqin Li; Yuan Yan (Frontiers Media S.A., 2024)
ObjectivesDepression is a major mental health concern among university freshmen, with negative life events recognized as a risk factor. However, limited studies have explored the underlying mechanisms between them. This study aims to investigate the longitudinal relationship between negative life events and depression, and to examine both the potential mediating role of perceived social support and the moderating role of self-esteem in this process.MethodsA two-wave longitudinal design with a 6-month interval was employed, involving 785 Chinese university freshmen (55.92% were female). Self-reported measures of negative life events, perceived social support, self-esteem, and depression were collected using validated scales.ResultsResults revealed that negative life events significantly predicted depression in freshmen after 6 months, with perceived social support partially mediating this relationship. In addition, self-esteem moderated the effect of negative life events on perceived social support. As self-esteem increased, there was a stronger mediating effect of perceived social support between negative life events and depression.DiscussionThis study verified a moderated mediation process of how negative life events impact depression among freshmen. The findings provide valuable insights for developing effective interventions to reduce the depression risk of freshmen.